Character learning model based on traditional songs in Indonesia - Adi Kistoro, Hanif Cahyo; Benny, Benny; Warnis, Warnis; Ulfah, Syofia; Zuhrah, Fatimah (Institute of Advanced Engineering and Science, 2024)
Character education is mandatory material in Indonesia. One of the character learning strategies is to use folk songs. This study describes the strategies used by teachers in implementing character learning and explores information about obstacles and supports in its application. There were 12 study participants consisting of religion teachers from six schools in the Yogyakarta and Sumatra Regions. Selection of participants using purposive sampling. Data collection through in-depth interviews using an interview guide. The analysis technique is carried out through the process of reducing, presenting and interpreting data to draw conclusions. The results of this study are very important for education, where the teacher’s strategy, the use of traditional songs can become a new model of character education. Obstacles faced in the form of diverse student abilities can increase innovation, creativity and teacher competence in designing learning. The results of this study can become a basic reference in a new character education strategy. This research has several limitations both from the location, research subjects and the type of research. Subsequent research with a more complete design will add to the strengthening of the results of this study.